Induced Partial Saturation: From Mechanical Principles to Engineering Design of an Innovative and Eco-Friendly Countermeasure against Earthquake-Induced Soil Liquefaction - Lucia Mele; Stefania Lirer; Alessandro Flora (Geosciences, 2024)
Earthquake-induced soil liquefaction is a catastrophic phenomenon that can damage existing building foundations and other structures, resulting in significant economic losses. Traditional mitigation techniques against liquefaction present critical aspects, such as high construction costs, impact on surrounding infrastructure and effects on the surrounding environment. Therefore, research is ongoing in order to develop new approaches and technologies suitable to mitigate liquefaction risk. Among the innovative countermeasures against liquefaction, Induced Partial Saturation (IPS) is considered one of the most promising technologies. It consists of introducing gas/air bubbles into the pore water of sandy soils in order to increase the compressibility of the fluid phase and then enhance liquefaction resistance. IPS is economical, eco-friendly and suitable for urbanised areas, where the need to reduce the risk of liquefaction must be addressed, taking into account the integrity of existing buildings. However, IPS is still far from being a routine technology since more aspects should be better understood. The main aim of this review is to raise some important questions and encourage further research and discussions on this topic. The review first analyses and discusses the effects of air/gas bubbles on the cyclic behaviour of sandy soils, focusing on the soil volume element scale and then extending the considerations to the real scale. The use of useful design charts is also described. Moreover, a section will be devoted to the effect of IPS under shallow foundations. The readers will fully understand the research trend of IPS liquefaction mitigation and will be encouraged to further explore new practical aspects to overcome the application difficulties and contribute to spreading the use of this technology.